Data for lexicography; The central role of the corpus - Lauder, Allan F. (Wacana, Journal of the Humanities of Indonesia, 2010)
This paper looks at the nature of data for lexicography and in particular on the central role that electronic corpora can play in providing it. Data has traditionally come from existing dictionaries, citations, and from the lexicographer's own knowledge of words, through introspection. Each of these is examined and evaluated. Then the electronic corpus is considered. Different kinds of corpora are described and key design criteria are explained, in particular the size of corpus needed for lexicography as well as the issue of representativeness and sampling. The advantages and disadvantages of corpora are weighed and compared against the other types of data. While each of these has benefits, it is argued that corpora are a requirement, not an option, as data for dictionary making.